Mach inability Studies on Metal Matrix Composite’s Using Abrasive Water Jet Machining - M.C., Kalai selvan; X, Hendry Thomas; B, Siddharthan; P, Divya Kumar (Bulletin of Scientific Research, 2019)
The non-traditional machining of particulate reinforced metal matrix composites is relatively new. This paper covers studies on match inability of aluminium - Boron carbide metal matrix composites (Al-B4C MMCs) with abrasive water jets (AWJs). Two different compositions of Al-B4C MMCs were processed with various mesh size, abrasive flow rate, transverse rate and water pressure with a view to identify the performance of the abrasive water jet machine for effective processing of MMCs with AWJs. The maximum penetration ability of AWJs in different MMCs was examined by conducting the experiments on trapezoidal shaped Al-B4C MMC specimens, prepared with stir casting method. Optical micrographs of MMC samples and scanning electron microscopic (SEM) examination of AWJ cut surfaces enabled to explain the trends of material removal by the abrasives. Analysis of results clearly indicated the choice of 80 mesh size abrasives, higher water pressure and flow rate and lower transverse rate for effective processing of Al-B4C MMCs with AWJs.